Parental Property Grants to Children as an Alternative Inheritance Mechanism - Muchamad Imron; Agus Purnomo; Abid Rohmanu (Journal of Economics, Law, and Humanities, 2026)
T Background/Introduction: The practice of parental property grants (hibah) to children has increasingly become an alternative inheritance mechanism aimed at preventing disputes among heirs. In Jogoyasan Village, Magelang Regency, this practice has developed as a hereditary tradition closely associated with social, cultural, and religious values that support family harmony and social stability. Research Objectives: This study aims to analyze the social functions of parental property grants to children and examine how social structures and community norms influence the implementation of hibah as an alternative to inheritance distribution. Methodology: This research employed a qualitative field research approach conducted in Jogoyasan Village. Data were collected through in-depth interviews and documentation involving parents as grantors, children as recipients, and community leaders. The data were analyzed using Talcott Parsons’ structural functionalism theory to understand the role of hibah in maintaining social equilibrium within society. Results: The findings reveal that hibah plays an important role in maintaining family relationships, preventing inheritance conflicts, and strengthening social responsibility among family members. Social structures based on deliberation, justice, and equality support the successful implementation of hibah practices. Local norms and religious values also work harmoniously in shaping a fair and balanced property distribution system. Unique Contribution: This study offers a sociological perspective on hibah by positioning it not merely as a legal alternative to inheritance, but also as a strategic mechanism for preserving social integration and stability within the community. Conclusion: Hibah practices in Jogoyasan Village function as an effective mechanism for maintaining family harmony and social stability through the integration of social norms, cultural values, and religious principles. Recommendations: Future studies are recommended to explore comparative hibah practices in different cultural settings and examine their implications for contemporary Islamic inheritance systems.